2009
DOI: 10.3109/08037050903424117
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with control of blood pressure among elderly people diagnosed with hypertension in a rural area of South Korea: The Chungju Metabolic Disease Cohort Study (CMC study)

Abstract: In elderly people diagnosed with hypertension general obesity (high BMI) appears to have an important influence on uncontrolled hypertension in men, whereas abdominal obesity (high waist circumference) appears to be an important factor in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Control of blood pressure among elderly has been shown to be safe and beneficial, 26,27 and various guidelines have reaffirmed that except for frail elderly, and all must achieve optimum control. 28e30 While innovative hypertension treatment programs for rural elderly have been initiated in middle income countries such as China 31 and Korea, 32 there is a need for such an initiative in India.…”
Section: Discussionmentioning
confidence: 99%
“…Control of blood pressure among elderly has been shown to be safe and beneficial, 26,27 and various guidelines have reaffirmed that except for frail elderly, and all must achieve optimum control. 28e30 While innovative hypertension treatment programs for rural elderly have been initiated in middle income countries such as China 31 and Korea, 32 there is a need for such an initiative in India.…”
Section: Discussionmentioning
confidence: 99%
“…The association between being overweight or obese and poor blood pressure control was reported in a Chinese study (Xu et al., ) and a Korean study (Lee et al., ). Our study did not find a statistically significant association between BMI and blood pressure.…”
Section: Discussionmentioning
confidence: 77%
“…Certain demographic characteristics also are associated with hypertension. For example, among Asians, old age is associated with poor blood pressure control (Dong et al., ) and male gender is associated with higher levels of systolic blood pressure among Chinese immigrants in the USA (Li, Wallhagen, & Froelicher, ), and high body mass index (BMI) is associated with uncontrolled blood pressure in Chinese men and in elderly men in South Korea (Lee et al., ; Xu et al., ). Another Chinese study reported that poor blood pressure control occurs among those who are young, live in urban areas, have minimal education, and are overweight or obese (Wang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Available linear relationship between body weight and blood pressure, that every 4.5 kg an increased body weight results in a 4 mmHg increased SBP [10]. As for central obesity, based on research conducted in China, central obesity in women (abdominal circumference ≥ 80 cm) increases the risk of uncontrolled hypertension [18]. Whereas in other studies in Sweden, it was found that among men, uncontrolled hypertension was associated with central obesity and increased the risk by 1.85 times [19].…”
Section: Risk Of Uncontrolled Hypertension and Obesitymentioning
confidence: 99%